Pengembangan Teknologi ERP Untuk Modul Accounting Management Studi Kasus CV MLB Sampit - Tuti Susanti; Mustaqiem Mustaqiem (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
The need for information about technology has now become commonplace, sometimes existing technology has not been fully utilized. With the increasing popularity of technology, it is possible for all businesses engaged in the service sector to be infected with technology fever. However, the company CV. MLB Sampit is still constrained by the presentation of financial report data. Financial reports are slow to figure out, searches regarding expenses and income are also difficult to find. In addition, mistakes often occur in making payment transactions due to the absence of a computerized system. To solve this problem, we need an accounting management system. Where later it can process financial transaction data, present financial data reports including journal reports, ledger reports, trial balance reports, loan reports and income statements. In building this application program, using PHP and Javascript as a programming language media and MySQL is used as database management. With the creation of this system is expected to facilitate the company CV. MLB Sampit in the process of recording transactions and financial reports.